The Routledge guide to the European Union - Bond, Ian; Leonard, R. L.; Taylor, Robert (Routledge, 2025)
Written by experts, this long-established and definitive guide to the workings of the European Union provides comprehensive, straightforward and readable coverage of this sometimes misunderstood and complex institution.This fully revised second edition explains not only what happens but why, analysing the EU's strengths and weaknesses, as well as opportunities for it to be more effective. With the EU's very existence under pressure due to Euroscepticism, continued crises with migration and borders, the re-emergence of the far right, and renewed great power competition in Europe and the world, it specifically outlines: How the EU has evolved over the last 70 years How it works: the institutions, the mechanisms Every area of EU competence from agriculture to defence The effects of the single market, a single currency and the successes and stresses of the eurozone The impact of the enlargement of the EU, prospects for further enlargement and closer political integration Reforming the EU's decision-making and defending the rule of law The EU's place in an ever more disorderly world The Routledge Guide to the European Union is well-established as the clearest and most comprehensive guide to how the EU operates. This new edition brings you up to date at a crucial stage in its history, at a time when it has never been under greater internal and external threat, but conversely is perhaps more important than ever.